Bioorthogonal Lanthanide Molecular Probes for Near‐Infrared Fluorescence and Mass Spectrometry Imaging. (6th September 2022) - Jin, Guo‐Qing; Sun, De‐en; Xia, Xiaoqian; Jiang, Zhi‐Fan; Cheng, Bo; Ning, Yingying; Wang, Fuyi; Zhao, Yao; Chen, Xing; Zhang, Jun‐Long
Abstract: We report here the development of clickable and highly near‐infrared (NIR) fluorescent lanthanide (Ln) complexes for bioorthogonal labeling of biomolecules. These azide‐ or alkyne‐functionalized Ln complexes are hydrophilic and fluorogenic, exhibiting a strong increase of NIR fluorescence upon conjugation with biomolecules. Metabolic labeling of biomolecules with azide or alkyne, followed by click labeling with the Ln complexes, enables NIR fluorescence (NIRF) imaging of DNA, RNA, proteins, and glycans in cells. Furthermore, multicolor imaging is performed by combining click‐labeling with the Ln complexes and immunostaining. In addition, the Ln complexes is compatible with click‐expansion microscopy (click‐ExM), which enables high‐resolution NIRF imaging of cellular glycoproteins. Finally, the Ln complexes can be used for time‐of‐flight secondary‐ion mass spectrometry (ToF‐SIMS) imaging, thus achieving the first example of dual‐modal imaging combining NIRF and SIMS microscopies. Abstract : Here, we developed clickable near‐infrared (NIR) lanthanide (Ln) complexes for bioorthogonal labeling. In combination with metabolic labeling, these NIR Ln (Ln=Yb, Er) complexes enabled NIR fluorescence (NIRF) imaging of proteins, glycans, and nucleic acids in cells. Furthermore, they were applied for multicolor imaging and NIR click‐expansion microscopy (click‐ExM). By combining these Ln probes with time‐of‐flight secondary‐ion mass spectrometry (SIMS), we achieved the first dual‐modal NIRF‐SIMS imaging.